‘I realised then how “Parisian” Egypt was’ : challenges and rewards of de-westernising travel journalism - Duffy, Andrew (2019)
Bypassing the dominant Western bias in journalism scholarship is a challenge; it raises the question of what might replace it. Similarly, to evade the Western post-imperialism orthodoxies recurrent in cultural studies scholarship into travel and tourism would require other perspectives. This study combines the two and attempts to circumvent the Western bias in scholarship on travel journalism, given that its constituent parts are – for different reasons – becoming de-centred from the West. Textual analysis of Singaporean newspaper articles in Mandarin and English shows that questions of privilege and power remain but need not be associated with narratives of post-imperialism. Instead, destinations are textually constructed to justify the writer’s decision to travel. The intention for this article is to suggest ways that dominant Western perspectives in media studies may be balanced by other viewpoints which still expose issues of power and privilege but offer a less hegemonic, more culturally neutral starting point.